Pengaruh PAD, DBH, DAU dan DAK Terhadap Belanja Modal Daerah Sumatera Utara Tahun 2017-2019 - Nina Purnasari; Elfrika Sitompul; Desy Krisda Laowo (Politeknik Ganesha Medan, 2022)
The purpose of this study was to determine and analyze the effect of Regional Original Income (PAD), Revenue Sharing Funds (DBH), General Allocation Funds (DAU) and Special Allocation Funds (DAK) on North Sumatra Regional Capital Expenditures. In this study, the population used is all district and city governments in North Sumatra Province and has a complete APBD report during the research period during the 2017-2019 period. The sampling technique was saturated sampling and the number of samples used in this study were 33 districts and cities in North Sumatra Province which were divided into 25 districts and 8 cities. This study uses the method of documentation. The data consists of a report on the realization of the regional revenue and expenditure budget. This study uses a quantitative approach and the type of research used is descriptive statistical method. The results of the study show that PAD partially does not have a positive effect on district/city capital expenditures in North Sumatra Province 2017-2019. DBH partially positive and significant effect on district/city capital expenditure in North Sumatra Province 2017-2019. The DAU partially has a positive and significant effect on district/city capital expenditures in North Sumatra Province 2017-2019. DAK partially does not have a positive effect on district/city capital expenditure in North Sumatra Province 2017-2019. And simultaneously PAD, DBH, DAU and DAK have a positive effect on district/city capital expenditure in North Sumatra Province 2017-2019.